Harnessing SSB tax for health and economic prosperity: A Path to sustainable growth - Alaika, Abdullah Aziz; Firmansyah, Amrie (WIM Solusi Prima, 2024)
This study explores the implementation of sugar-sweetened beverages (SSB) excise taxes as a policy tool to address public health challenges related to excessive sugar consumption in Indonesia. With rising rates of diabetes and obesity, SSB taxes have been widely adopted globally, yielding positive outcomes such as reduced consumption and increased government revenue. This research synthesizes global evidence through a scoping review and examines how an SSB excise tax could be structured to fit Indonesia’s unique socio-economic context. The findings suggest that a tiered tax based on sugar content would be most effective in curbing consumption while encouraging the beverage industry to innovate healthier alternatives. Revenue generated from the tax, estimated to reach IDR 9.68 trillion annually, could be directed toward public health initiatives, particularly for preventing and managing non-communicable diseases. The study also recommends complementary public health campaigns to raise awareness of the risks associated with sugar consumption. Effective collaboration between the Directorate General of Taxes and the Ministry of Health is crucial for successfully implementing and monitoring the policy. The introduction of SSB excise taxes in Indonesia represents a strategic opportunity to enhance public health, generate substantial government revenue, and support long-term sustainable development.